Characterization of imatinib-resistant K562 cell line displaying resistance mechanisms - Hekmatshoar, Yalda; Ozkan, Tulin; Altinok Gunes, Buket; Bozkurt, Sureyya; Karadag, Aynur; Karabay, Arzu Zeynep; Sunguroglu, Asuman (Cellular and Molecular Biology, 2018)
Chronic myeloid leukemia (CML) is a hematopoietic malignancy characterized by the t(9; 22) and the related oncogene, BCR-ABL. Tyrosine kinase activity of fusion protein BCR-ABL is the main cause of CML. Even if imatinib is used as a tyrosine kinase inhibitor (TKI) for CML therapy, drug resistance may occur in patients and the clinical failure of imatinib treatment in resistant patients had resulted with the use of another alternative TKIs. BCR-ABL dependent and independent molecular mechanisms have crucial roles in drug resistance. To reveal the underlying molecular mechanisms which play significant roles in imatinib resistance in CML, we established K562 imatinib-resistant cell line (K562r5) which was continuously exposed to (5µM) imatinib to investigate molecular mechanisms which play significant roles in drug resistance. First of all, we analyzed T315I, M351T, F315L and F359C/L/V mutations with DNA sequencing as a BCR-ABL dependent mechanism in our cell lines. Moreover, we investigated BCR-ABL independent mechanisms such as apoptosis, autophagy, drug transport and DNA repair which affect drug resistance in these cell lines. In vitro cell viability was determined by MTT assay. DNA sequencing analysis was performed to detect BCR-ABL mutations. The apoptotic effect of imatinib on CML cell lines was tested by flow cytometric Annexin V-PE staining and caspase activation assays. Apoptotic, autophagic, drug transporter and DNA repair genes expression levels were determined by RT-PCR. The conventional cytogenetic analysis was performed on K562s and K562r cells. Our results indicate that inhibition of apoptosis, induction of autophagy, overexpression of efflux gene MDR1 and down-regulation of influx gene OCT1 play crucial roles in the progression of imatinib resistance.